Dynamics of Resistance to The Poetry “A Jacket Stained with Blood” by Taufiq Ismail - Gracesela Septiana Sibuea; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2026)
This article analyzes the dynamics of resistance to the 66th generation through the poem